Absolute Dermatology Review: Mastering Clinical Conditions on the Dermatology Recertification Exam - Gloster, Jr., Hugh Morris (Springer, 2015)
​​​Each dermatologist that was board certified after 1992 is required by the American Board of Dermatology to take a recertification exam every ten years. One of the major components of the exam is to be able to identify clinical photographs of approximately 200 skin diseases, and while there are other components to the test, they vary according to subspecialty. However, everyone is required to identify the images, so several months before the exam, the American Board of Dermatology releases a list of the skin diseases that will be tested, but does not provide the images or reveal which ones will appear.